Elucidation of type of molecular interactions for the imprinting of shikimic acid - Saw, Mei Huey (2020)
During the preparation of shikimic acid imprinted polymer, the effect of rebinding solution water content on the rebinding performance of shikimic acid (SA) imprinted polymer was studied. Result showed that the highest affinity toward SA was in a 100% aqueous rebinding solution, suggesting that the interactions occurred between SA and the polymer were ionic and/or hydrophobic in nature. Further study on the effect of rebinding solution pH to the SA imprinted polymer rebinding performance showed that the performance of the SA imprinted polymer depended on the rebinding solution pH and the highest affinity occurred at pH 4.0; this confirmed that ionic interaction played an important role in the rebinding of SA. Taking into account the deductions made from the combined results of the rebinding solution water content and effect of pH, together with observation of the red shift in the SA spectral during ultraviolet-visible spectroscopic titration experiments, suggest that the specificity shown by SA imprinted polymer in the aqueous solution was due to both ionic and π−π hydrophobic interactions.